A Case Study of a Critical Discourse Analysis of Political Discourse: Boris Johnson's Resignation Speech (The International Journal for Scientific Research, 2023)
The paper is a study of qualitative with descriptive data presentation. The author uses power to invest the pronouns of Boris Johnson's resignation speech. The Cognition Theory by (Teun A Van Dijk, 2009) was used. Textually, social cognition and social context are three component aspects in revealing the implied meaning of the use of personal pronouns in Boris Johnson's Resignation speech. The data was collected from Boris Johnson's Resignation speech on the 7th of July,2022. This transcript was collected from the media. The study's objective is to describe the personal pronouns used by Boris Johnson in his Resignation speech to find out the unexposed meaning of the relied personal pronouns. In this current paper, different pronouns (I, we, us, me, I'm) were used, and each has a specific function and target, and I have found that each personal pronoun used by Boris Johnson refers to a certain ideology and strategy. The reason behind using such pronouns is to attract the audience and supports them to achieve the wanted target in the policy. Also, Johnson tried to convince supports that he and his party in the right way.
Keywords: Audience; CDA; personal pronouns; Resignation; supporters